Editorial: comprehensive research of Antarctica - Aleksei V. Bolshunov; German L. Leitchenkov (Записки Горного института)
Antarctica is the least studied continent on the planet. Extreme climate conditions, ice cover, and the lack of permanent infrastructure make it difficult to conduct field and stationary research. Nevertheless, interest in Antarctica as a unique natural laboratory is steadily growing, which is confirmed by a stable increase in the number of scientific publications covering a wide range of topics from geodynamics and glaciology to applied engineering solutions.